The genetic aetiology of cannabis use initiation: a meta‐analysis of genome‐wide association studies and a SNP‐based heritability estimation. (24th July 2012) - Verweij, Karin J. H.; Vinkhuyzen, Anna A. E.; Benyamin, Beben; Lynskey, Michael T.; Quaye, Lydia; Agrawal, Arpana; Gordon, Scott D.; Montgomery, Grant W.; Madden, Pamela, A. F.; Heath, Andrew C.; Spector, Timothy D.; Martin, Nicholas G.; et al.
Abstract: While initiation of cannabis use is around 40% heritable, not much is known about the underlying genetic aetiology. Here, we meta‐analysed two genome‐wide association studies of initiation of cannabis use with > 10 000 individuals. None of the genetic variants reached genome‐wide significance. We also performed a gene‐based association test, which also revealed no significant effects of individual genes. Finally, we estimated that only approximately 6% of the variation in cannabis initiation is due to common genetic variants. Future genetic studies using larger sample sizes and different methodologies (including sequencing) might provide more insight in the complex genetic aetiology of cannabis use.